Communication Audit Using Sadix Application Marketing Division PT Enzim Bioteknologi Internusa in Central Java & DIY - Edi Karyono; Septi Kurnia Prastiwi (Social Science Studies, 2021)
The communication audit process is designed to examine and evaluate the communication program, to reveal obstacles in achieving effective communication, to reveal gaps in the communication process and to provide recommendations to PT Enzyme Biotechnology Internusa. The results of the communication audit at PT Enzyme Biotechnology Internusa are broadly speaking the marketing team in the Central Java and DIY areas are satisfied with the communication that occurs in the company, only at some points that are not satisfied, one of which is the integrity of the organization. The recommendation from the communication audit is to improve the quality of vertical communication, the Sadix application should still be used even though it has not directly improved performance but can increase discipline and monitor marketer team visits.